2017
DOI: 10.1111/bjh.14810
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of externalized phosphatidylserine density on red blood cell‐derived microparticles in SCA patients treated with hydroxycarbamide

Abstract: 7.4 (6.9-8.0) 7.6 (7.0-8.5)** 7.9 (6.85-9.1)* 7.6 (7.4-8.7)** 7.7 (7.2-8.2)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…These conflicting results could be accounted for by the large interindividual variation in MPs concentration in SCD. However, a longitudinal study reported no change in MPs concentration in patients receiving HU for 24 months [ 134 ]. To further characterize the biomarker status of MPs, an observational study with an estimated enrollment of 360 participants has also been initiated (NCT012422878).…”
Section: Pathophysiology Of Scdmentioning
confidence: 99%
See 1 more Smart Citation
“…These conflicting results could be accounted for by the large interindividual variation in MPs concentration in SCD. However, a longitudinal study reported no change in MPs concentration in patients receiving HU for 24 months [ 134 ]. To further characterize the biomarker status of MPs, an observational study with an estimated enrollment of 360 participants has also been initiated (NCT012422878).…”
Section: Pathophysiology Of Scdmentioning
confidence: 99%
“…Our group reported that SCA patients with frequent VOCs had increased levels of PLT-MPs, compared to SCA patients with rare crises [ 141 ]. In SCA patients, we showed using two longitudinal cohorts, that circulating PLT- and RBC-MPs PS exposure level was increased during VOC, but decreased after two years under HU treatment, when compared to steady-state conditions [ 39 , 134 , 140 ]. Therefore, PS exposure by these MPs subtypes seems to be a promising marker of clinical severity and of HU treatment efficacy.…”
Section: Pathophysiology Of Scdmentioning
confidence: 99%
“…HU improved blood rheology: increased Hct without any increase in blood viscosity and increased RBC deformability Another positive effect of HU treatment is that it reduces PS density on RBC MPs HU also contributes to reduce circulating cell adhesiveness.…”
Section: Therapiesmentioning
confidence: 99%
“…While pre-incubation of m/lEVs with annexin-V, a PS blocker, abolished the induced endothelial ICAM-1 overexpression, we have shown that the proinflammatory properties of m/lEVs collected during a vaso-occlusive crisis, a condition associated with high PS externalization of m/lEVs ( 114 ), were exacerbated. In contrast, these proinflammatory properties were considerably reduced for m/lEVs obtained from patients treated with HU, which exhibited low PS externalization ( 116 ). In addition, we presented evidence that the endothelial activation mediated by these EVs also involved TLR4 signaling pathway ( 125 ).…”
Section: Extracellular Vesicles As Bio-effectors Of Scdmentioning
confidence: 99%
“…Knowing the wide distribution of m/lEV concentration in SCA patients ( 103 , 112 , 113 ), these contradictory results could be related to the cross-sectional design of these studies. In order to reduce the inter variability, we have implemented a longitudinal follow-up of SCA patients before and after 2 years of HU treatment ( 116 ). While no change in m/lEV concentration was detected, two qualitative parameters of m/lEVs originated from RBCs were modified during the course of HU treatment: EVs size was increased and their PS exposure was decreased.…”
Section: Extracellular Vesicles In Scdmentioning
confidence: 99%